The Philosophy of Thomas Reid
VIII, 492 p.
Keywords: Note on references to the works of Thomas Reid 5 SECTION 1 - Perception Yves Michaud (University of Paris, France) 9 'Reid's Attack on the Theory of Ideas' William P. Alston (Syracuse University, U. S. A. ) 35 'Reid on Perception and Conception' Vere Chappell (University of Massachusetts, U. S. A. ) 49 'The Theory of Sensations' Norton Nelkin (University of New Orleans, U. S. A. ) 65 'Reid's View of Sensations Vindicated' A. E. Pitson (University of Stirling, Scotland) 79 'Sensation, Perception and Reid's Realism' Aaron Ben-Zeev (University of Haifa, Israel) 91 'Reid's Opposition to the Theory of Ideas' Michel Malherbe (University of Nantes, France) 103 'Thomas Reid on the Five Senses' SECTION 2 - Knowledge and COlIIOOn Sense Keith Lehrer (University of Arizona, U. S. A. ) 121 'Reid on Evidence and Conception' Dennis Charles Holt (Southeast Missouri State 145 University, U. S. A. ) 'The Defence of Common Sense in Reid and Moore' T. J. Sutton (University of Oxford, England) 159 'The Scottish Kant?' Daniel Schulthess (university of Berne, Switzerland) 193 'Did Reid Hold Coherentist Views?' VI Claudine Engel-Tiercelin (University of Rouen, France) 205 'Reid and Peirce on Belief' C. A. J. Coady (University of Melbourne, Australia) 225 'Reid on Testimony' SECTION 3 - Mind and Action James Somerville (University of Hull, England) 249 'Making out the Signatures: Reid's Account of the Knowledge of Other Minds' R. F.